Suction through point-like opening and stability of boundary layer (Archives of Mechanics - Test, 2001)
A model of boundary layer suction through small opening is suggested. A procedure of neutral curve construction is described. The dependence of the shift of neutral curves on the intensity of suction and on the position of the opening is studied.